#BlackLivesMatter : protesting racism - Thomas, Rachael L. (#Movements., 2020)
Explores the history of racism in America and the creation and growth of the #BlackLivesMatter movement. Discusses the mission and actions of the Black Lives Matter group, the backlash against them, and the other movements it has inspired. Also discusses how social media has driven the movement forward. Includes color photographs, a timeline, a glossary, and online resources.